2019
DOI: 10.18821/0869-2084-2019-64-1-34-41
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Endothelial Dysfunction: Pathogenetic Role and Diagnostic Significance

Abstract: Endothelial dysfunction (ED) is considered one of the pathogenetic mechanisms of a whole range of diseases. Detection of specific biochemical markers in the blood is an effective way to ED diagnostics that characterize the vascular endothelium state. This review highlights the pathogenetic role of the factors synthesized by endotheliocytes whose level changes in biological fluids reflect violations of the endothelium basic physiological properties: vasomotor function, thromboresistance, angiogenesis regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 41 publications
0
6
0
4
Order By: Relevance
“…The determination of various factors secreted by the endothelium in biological fluids, namely the blood serum, is a very important method for determining the degree of endothelial dysfunction severity (Ivanov et al 2014;Kazimli et al 2014;Vasina et al 2017). The determination of specific blood biochemical markers is an effective method to detect endothelial dysfunction which is used to characterize the state of the vascular endothelium (Stepanova et al 2019). Among these markers, there is ET-1 that reflects the state of endothelial vasomotor function (Sokolov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The determination of various factors secreted by the endothelium in biological fluids, namely the blood serum, is a very important method for determining the degree of endothelial dysfunction severity (Ivanov et al 2014;Kazimli et al 2014;Vasina et al 2017). The determination of specific blood biochemical markers is an effective method to detect endothelial dysfunction which is used to characterize the state of the vascular endothelium (Stepanova et al 2019). Among these markers, there is ET-1 that reflects the state of endothelial vasomotor function (Sokolov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Наряду с этими морфометрическими изменениями содержание маркера, указывающего на повреждение эндотелия, -гомоцистеина в плазме крови -увеличивается в группе отравления бихроматом натрия, что свидетельствует о его высоком общем действии и указывает на прямое влияние гомоцистеина на изменения в стенке кровеносных сосудов. По литературным данным, к числу маркеров эндотелиальной дисфункции относится гомоцистеин наряду с С-реактивным белком, 8-гидрокси-и 2-дезоксигуанозином [12,13]. Кроме того, повышенные уровни гомоцистеина в плазме являются основным фактором развития атеросклероза, а эндотелиальная дисфункция основана на гомо цис теинзависимом повреждении сосудов [14,15].…”
Section: результаты и обсуждениеunclassified
“…Clinical studies and animal experiments have shown that a variety of cardiovascular and cerebrovascular diseases (chronic cardiac insufficiency, diabetic vascular complications, stroke) are accompanied by endothelial cell dysfunction ( Jara and Mezzano, 2008 ; Moon, 2021 ). In clinical studies, surface high-frequency ultrasound may be used to detect brachial artery blood flow–mediated endothelium-dependent dilation (FMD) and non–endothelium-dependent diastolic function (nitroglycerin-mediated dilation, NMD) to detect nitric oxide in blood (nitric oxide, NO), von Willebrand factor (vWF), asymmetric dimetylarginine (ADMA), and other indirect indicators of endothelial function ( Arslan et al, 2017 ; Mortensen et al, 2019 ; Stepanova et al, 2019 ). The morphological changes of endothelial injury have been observed and endothelial NO levels and endothelial NO synthase (eNOS) activity were detected in different experimental animal models (hypertension, atherosclerosis, diabetes) ( Kietadisorn et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%